Fecal microbiota transplantation is a promising therapy for kidney diseases - Jiawei Zhang; Jiawei Zhang; Xiangge Ren; Xiangge Ren; Bing Li; Bing Li; Zhifen Zhao; Zhifen Zhao; Shoudao Li; Shoudao Li; Wensheng Zhai; Wensheng Zhai (Frontiers in Medicine, 2025)
Kidney diseases, including acute kidney injury (AKI) and chronic kidney disease (CKD), pose growing global public health challenges. With the emergence and expanding understanding of the “microbiota–gut–kidney axis,” increasing evidence indicates that intestinal barrier disruption, abnormal microbial metabolite production, and intestinal mucosal immune dysregulation play critical roles in the pathogenesis of various kidney diseases. Therapeutic modulation of the gut microbiota through probiotics, prebiotics, synbiotics, and natural products has shown potential for slowing kidney disease progression. Fecal microbiota transplantation (FMT), a direct method of reconstructing gut microbial communities, has demonstrated promise in CKD by targeting mechanisms such as inhibition of the renin–angiotensin system (RAS), attenuation of inflammation and immune activation, and restoration of intestinal barrier integrity. Although FMT has not yet been applied to AKI, its use in CKD subtypes, such as diabetic nephropathy, IgA nephropathy, membranous nephropathy, and focal segmental glomerulosclerosis, has shown encouraging preclinical and preliminary clinical results. This review systematically summarizes the current research on FMT in the context of kidney disease, evaluates its therapeutic mechanisms and feasibility, and highlights its limitations. Most studies remain in the preclinical stage, while available clinical trials are limited by small sample sizes, heterogeneous designs, and lack of standardization. To enhance the translational potential of FMT in nephrology, future studies should incorporate artificial intelligence for personalized intervention strategies and establish standardized protocols to ensure safety, efficacy, and reproducibility.